THE PERFORMANCE OF CASSAVA FLOUR AS A WATER-REDUCING ADMIXTURE FOR CONCRETE (Nigerian Journal of Technology, 2009)
The performance of cassava flour as a water reducing admixture in concrete was investigated.  Four concrete mixes of widely differing water/cement ratios were made and each of the mixes contained three different dosage levels of cassava flour as admixture.  The properties tested include workability of the fresh concrete, saturated density and compressive strength of the hardened concrete.  These properties were compared with those of similar concrete mixes made without admixture.  It was observed that cassava flour has appreciable fluidifying action in the fresh concrete so that, under appropriate conditions, it either considerably improved the workability of the fresh concrete at normal water content or permitted a water reduction of at least 8% to be made while maintaining a given workability.  Results of the tests also show that the 28 day compressive strength of concretes containing cassava flour admixture is higher than those of control concretes and that the compressive strength values obtained at 28 days exceeded those to be expected from water reduction alone.